The Influence Of Perceived Ease Of Use And Trust On Intention To Re-Use The Dana E-Wallet Application Through Customer Satisfaction As An Intervening Variable Among Student Users In Pontianak - Sari, Nilam; Fachri, Helman (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The advancement of technology has driven consumer behavior changes toward digital transactions, including the use of e-wallets. Although the Dana application has become one of the most popular e-wallets in Pontianak, with a 72% increase in users in 2023, complaints regarding ease of use, security, and user satisfaction persist. This study aims to analyze the influence of Perceived Ease of Use and Trust on Intention to Re-Use, with Customer Satisfaction as an intervening variable. The research employs a quantitative approach with 100 respondents selected through purposive sampling and analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results show that Perceived Ease of Use significantly affects Customer Satisfaction (T-Statistic = 3.519; P-Value = 0.000) but does not significantly impact Intention to Re-Use (T-Statistic = 0.330; P-Value = 0.742). Conversely, Trust significantly influences both Customer Satisfaction (T-Statistic = 6.094; P-Value = 0.000) and Intention to Re-Use (T-Statistic = 2.527; P-Value = 0.012). User satisfaction mediates the relationships among these variables, indicating that satisfaction and trust are key factors in enhancing user loyalty to the Dana application.